From lifestyle to creative economy: Consumer choices, services capes, and digital drivers in Pakistan’s coffee market - Watto , Waqas Ahmad (Privietlab, 2024)
This study reframes Pakistan’s urban coffee boom as a consumer culture phenomenon with concrete managerial and policy levers. Using a descriptive, integrative approach, we synthesize observations from a source presentation with established frameworks— the Theory of Planned Behavior (TPB), servicescape, the stimulus–organism–response (S–O–R) model, hedonic consumption, and experiential marketing—to explain why youth segments dominate demand and why sweet, milk-based iced have become the anchor offering. We argue that photogenic, comfort-optimized café environments act as dual-purpose assets: they enhance on-site affect (pleasure and arousal) and generate user-generated content that compresses customer-acquisition costs via social proof. Baristas function as cultural intermediaries, translating origin stories and crafts into authenticity cues that raise willingness to pay and loyalty. We propose a testable mechanism linking servicescape and social media exposure (stimuli) to hedonic motivation and perceived value (organism), and onward to repeat visits, basket size, and eWOM (response). Practical implications include instrumenting the store-to-content funnel, managing menu complexity while preserving hedonic payoffs, and building barista-led community programs. The limitations of this study include the reliance on descriptive materials and the absence of multi-city causal evidence. Future work should combine SEM, field experiments, and digital trace data to estimate the elasticities and quantify the media yield.